2006
DOI: 10.1677/joe.1.06565
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of the progesterone receptor in mouse and human reproductive organs

Abstract: The effects of gonadotropins on progesterone receptor (PR) expression and localization in the mouse oviduct, uterus, and ovary was examined. In the oviduct ciliated epithelial cells of adult mice and human revealed a unique PR localization to the lower half of the motile cilia whereas the nuclei were unstained or faintly stained. Pubertal female mice were further studied by confocal laser scanning microscopy and western blotting before and after injection with FSH and LH followed by human chorionic gonadotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
92
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 49 publications
11
92
1
2
Order By: Relevance
“…The role of PGR in ovulation has been extensively studied in mammals (Natraj and Richards, 1993;Gava et al, 2004;Teilmann et al, 2006). In addition, a handful of studies on the function of Pgr in teleosts have also been published Thomas, 1995, 1999;Toda et al, 2000;Chen et al, 2010;Hanna et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The role of PGR in ovulation has been extensively studied in mammals (Natraj and Richards, 1993;Gava et al, 2004;Teilmann et al, 2006). In addition, a handful of studies on the function of Pgr in teleosts have also been published Thomas, 1995, 1999;Toda et al, 2000;Chen et al, 2010;Hanna et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…P 4 reduces CBF through classical progesterone receptors (PGRs) expressed on the ciliated epithelial cells in a dosage-dependent manner in humans and mice (Mahmood et al 1998, Bylander et al 2010, 2013. A non-classical PGR is expressed in the lower part of the cilia stalk in mouse oviducts (Teilmann et al 2006). Recent studies in mice indicated that low dosage of P 4 and short activation time (within 30 min) are sufficient to reduce oviductal CBF (Bylander et al 2010(Bylander et al , 2013.…”
Section: Ciliary Beatingmentioning
confidence: 99%
“…The membranes of motile cilia of the mammalian oviduct contain progesterone receptors [mouse and human (Teilmann et al, 2006;Nutu et al, 2009)], estrogen receptor- [rat (Shao et al, 2007)] and interleukin-6 receptor (IL6R) [mouse and human (Shao et al, 2009)]. Furthermore, progesterone (Mahmood et al, 1998;Paltieli et al, 2000;Wessel et al, 2004) and interleukin-6 (Papathanasiou et al, 2008) regulate oviductal ciliary beat frequency.…”
Section: Motile Cilia In the Mammalian Oviductal Epithelium Exhibit Rmentioning
confidence: 99%